Intelligent Ambulance Management System in Smart Cities - Akça, Tugay; ŞAHİNGÖZ, ÖZGÜR KORAY; Koçyiğit, Emre; Tozal, Mücahid (Institute of Electrical and Electronics Engineers Inc., 2020)
According to the United Nations' expectation, the total population of the cities will be doubled in the next three decades. This accelerating growth causes crucial problems in the main components of both traditional cities and smart cities. To increase the living quality of the residence in smart cities, enabling a clean, healthy, and sustainable environment are the major fields for the smart cities' managers and directors. One of the main infrastructures of the smart city is identified as smart health, which can be enabled with the use of modern technologies such as Internet of Things, especially for accessing the patients when they need help. In this Project, a smart ambulance management system is proposed in a smart city environment. If a patient needs an ambulance, the operator finds the nearest ambulance and direct it to the patient. The coordinates of ambulances are dynamically traced by the system, and Google Maps, as a third-party service, is used in order to calculate the shortest path to the casualty. After reaching to the patient, the expert (doctor or nurse) investigates the situation and finds the best available hospital by the proposed system. The experimental results showed that the proposed system finds the best solution in an acceptable ×.
2020 International Conference on Electrical Engineering, ICEE 2020
Keywords: Smart Health; Smart Cities; Shortest Path; IoT; Ambulance Deployment